"Sustainable growth" or "growth with pollution"—— research on economic growth patterns of industrial enterprise based on industry attributes. Issue 1 (November 2020) - Yue, Qin; Chen, Jiameng
Abstract: In recent years, protecting the ecological environment while developing the economy has become a widespread demand, but there is still a big controversy about the mode of industrial economic growth in China. This paper analyzes the growth pattern of China's industrial enterprises by using the micro data of enterprises from 2011 to 2018. On the one hand, industrial enterprises without pollution fees show higher sales growth rate, and this phenomenon is more obvious in high pollution industries such as mining industry and smelting industry, which proves the existence of "sustainable growth" pattern; on the other hand, among the industrial enterprises that are levied pollution fees, those with more pollution fees have higher sales growth rates, which shows that there is still a phenomenon of "growth with Pollution" in some polluting enterprises. These enterprises evade the responsibility of protecting the environment by paying the pollution fees, and in exchange for the growth of the company's sales at the expense of the environment. This paper provides a reference for further promotion of energy saving, and selection of sales growth pattern for highly pollution industries such as mining industry and smelting industry.